Modeling and simulation of the endogenous CYP3A induction marker 4β-hydroxycholesterol during enasidenib treatment - Li Y (Dove Medical Press, 2019)
Yan Li,1 Jamie N Connarn,1 Jian Chen,2 Zeen Tong,2 Maria Palmisano,1 Simon Zhou1 1Translational Development and Clinical Pharmacology, Celgene Corporation, Summit, NJ, USA; 2Non-Clinical Development, Celgene Corporation, Summit, NJ, USA Background: Enasidenib (IDHIFA®, AG-221) is a first-in-class, targeted inhibitor of mutant IDH2 proteins for treatment of relapsed or refractory acute myeloid leukemia. This was a Phase I/II study evaluating safety, efficacy, and pharmacokinetics/pharmacodynamics (PK/PD) of orally administered enasidenib in subjects with advanced hematologic malignancies with an IDH2 mutation. Methods: Blood samples for PK and PD assessment were collected. A semi-mechanistic non-linear mixed effect PK/PD model was successfully developed to characterize enasidenib plasma PK and to assess enasidenib-induced CYP3A activity. Results: The PK model showed that enasidenib plasma concentrations were adequately described by a one-compartment model with first-order absorption and elimination; the PD model showed a high capacity to induce CYP3A (Emax=7.36) and a high enasidenib plasma concentration to produce half of maximum CYP3A induction (EC50 =31,400 ng/mL). Monte Carlo simulations based on the final PK/PD model showed that at 100 mg once daily dose there was significant drug accumulation and a maximum of three-fold CYP3A induction after multiple doses. Although the EC50 value for CYP3A induction by enasidenib is high, CYP3A induction was observed due to significant drug accumulation. Conclusion: CYP3A induction following enasidenib dosing should be considered when prescribing concomitant medication metabolized via this pathway. Keywords: enasidenib, modeling and simulation, CYP3A induction, 4β-hydroxycholesterol